Exploring Switching Intentions Among Generation Z Smartphone Users: A Push-Pull-Mooring Framework Analysis of Factors Across Smartphone Segments - Choo Ling Suan; Alice Reyna Gondokusumo; Hardijanto Saroso; Diena Dwidienawati; Dicky Hida Syahchari (Australasian Accounting, Business and Finance Journal, 2023)
This research uses the Push-Pull-Mooring Framework to explore the factors influencing smartphone users’ switching intentions, whether between levels of smartphone types within the same brand or across different brands. Using online survey data from 141 Generation Z Smartphone users in Jakarta, respondents have been divided into three segments according to the smartphone price. These are Entry-Level, Mid-Range, and High-End. This study uses the data triangulation research method by utilizing WrapPLS 7.0 and Nvivo 12 software. This study found that in every level of the smartphone, the Entry-level, Mid-range, and High-End, the most significant factor for switching intention is the Push factor. Apart from that, the quantitative analysis demonstrates that six other factors cause Smartphone users to change smartphone brands: convenience, features, durability, needs, user experience, and the price of smartphones.
Keywords: SDG 9; SDG 1; Switching intentions; Push-Pull-Mooring Factors; Smartphones; Generation Z